Syntheses of trans-SCH-A and cis-SCH-A via a stereodivergent cyclopropanation protocol. - Csatayová, K; Davies, S; Lee, J; Ling, K; Roberts, P; Russell, A; Thomson, J (2010)
A highly diastereoselective cyclopropanation protocol has been employed in the syntheses of trans-SCH-A and cis-SCH-A. This strategy encompasses a stereodivergent procedure for the preparation of syn- and anti-cyclopropane diastereoisomers in high dr from a common allylic carbamate precursor.